2013
DOI: 10.1177/156482651303400402
|View full text |Cite
|
Sign up to set email alerts
|

Chilean Complementary Feeding Program Reduces Anemia and Improves Iron Status in Children Aged 11 to 18 Months

Abstract: In Chile, the NCFP has had an impact on the reduction of anemia and improved the iron status of children aged 11 to 18 months. Increasing the consumption of this iron-fortified milk could enhance the impact of the NCFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Most of the studies used cross-sectional design, although one was a retrospective study [13], thirteen were national surveys about health, diet, and lifestyle [14,15,16,17,18,19,20,21,22,23,24,25,26], and five more were based on national surveys reports [27,28,29,30,31]. The studies were performed in Guyana [20], Argentina [29,32,33], Bolivia [26], Brazil [18,28,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50], Chile [51,52], Colombia [27], Costa Rica [53,54], Cuba [55,56], Dominican Republic [24,25], Ecuador [16,57], Uruguay [58], Jamaica [59], Dominica [13], El Salvador [23], Guatemala [22], Haiti [17,60], Honduras […”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies used cross-sectional design, although one was a retrospective study [13], thirteen were national surveys about health, diet, and lifestyle [14,15,16,17,18,19,20,21,22,23,24,25,26], and five more were based on national surveys reports [27,28,29,30,31]. The studies were performed in Guyana [20], Argentina [29,32,33], Bolivia [26], Brazil [18,28,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50], Chile [51,52], Colombia [27], Costa Rica [53,54], Cuba [55,56], Dominican Republic [24,25], Ecuador [16,57], Uruguay [58], Jamaica [59], Dominica [13], El Salvador [23], Guatemala [22], Haiti [17,60], Honduras […”
Section: Resultsmentioning
confidence: 99%
“…In Chile, until as late as 1999, about 30% of the children under 2 years of age presented with IDA, often as a result of poor maternal health condition or poor dietary intake. Public health policies of “ fortification” such as availability of formula milk at government health centers, caused prevalence of IDA in infants under 18 months of age to drop to 10% in a period of 10 years (Brito et al, 2013). Although the decreasing incidence is promising, it should be emphasized that iron is an important nutrient for brain development, and the impact of IDA in infancy development, even after iron therapy is of clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…This target population requires specialized food vehicles [1]. In infants and young children, the use of fortified complementary foods has been shown to be more effective compared to supplements [35]. Three large trials in children between 1 month and 4 years of age in Nepal, India and Africa demonstrated that children who received additional iron/folic acid plus zinc in the form of supplements experienced more adverse effects compared to those who received only placebo, raising concerns on potential negative zinc-iron interactions and questioning the safety of this strategy [36,37,38,39].…”
Section: Food Fortification As a Tool For Addressing Micronutrient Dementioning
confidence: 99%